Kualitas Pelayanan Publik di Kelurahan Kenangan Baru Kecamatan Percut Sei Tuan - Dewi Sartika Siregar; Julia Ivanna (Journal on Education, 2024)
This research aims to determine community satisfaction with services and how officers behave in providing services. Therefore, government officials should pay attention to the dimensions above to create community satisfaction. Of course, this is not something that is easy to do, because it requires a long process and time. to change the culture that has surrounded the attitude and behavior patterns of the government bureaucracy so far. This research method uses qualitative descriptive research methods in research aimed at providing a general overview of the nature of qualitative descriptive research methods in research on the quality of public services in Kenangan Baru Village, Percut Sei Tuan District, Deli Serdang Regency, data analysis in qualitative descriptive research with 5 people as the population and sample. With conclusions, however, until now the services that have been provided to the community are sometimes still difficult to access directly by the community and the procedures are sometimes complicated and often make it difficult for the community when they have to process certain letters or permits, unclear costs and the occurrence of illegal levies ( extortion), is currently a reflection of the low quality of service in Indonesia.